La qualification des cadres hiérarchiques par le Code du travail - Blouin, Rodrigue (Relations industrielles / Industrial Relations, 1975)
The Labor Code states that the word employee does not include « a person who, in the opinion of the investigation commissionner, is employed as manager, superintendant, foreman or representative of the employer in his relations with his employees ». To undertake the identification of employees affected by this definition, labor courts do not care much about job titles, but rather take a criterion as a basis : freedom of action in exercising management authority. Employees carrying on such a form of authority are called management members or line management.